A Co3O4-embedded porous ZnO rhombic dodecahedron prepared using zeolitic imidazolate frameworks as precursors for CO2 photoreduction. Issue 12 (7th March 2016) - Wang, Tao; Shi, Li; Tang, Jing; Malgras, Victor; Asahina, Shunsuke; Liu, Guigao; Zhang, Huabin; Meng, Xianguang; Chang, Kun; He, Jianping; Terasaki, Osamu; Yamauchi, Yusuke; et al.
Abstract : A novel porous ZnO@Co3 O4 composite is obtained from ZIF-8@ZIF-67 crystals and exhibits a distinguished photocatalytic activity and stability for CO2 reduction. Abstract : Metal–organic frameworks (MOFs) are attracting considerable attention for their use as both the precursor and the template to prepare metal oxides or carbon-based materials. For the first time in this paper, the core–shell ZIF-8@ZIF-67 crystals are thermally converted into porous ZnO@Co3 O4 composites by combining a seed-mediated growth process with a two-step calcination. The designed porous ZnO@Co3 O4 composites exhibited the highest photocatalytic activity with an excellent stability for the reduction of CO2 among the commonly reported composite photocatalysts. Their superior photocatalytic performance is demonstrated to be resulting from the unique porous structure of ZnO@Co3 O4 and the co-catalytic function of Co3 O4 which can effectively suppress the photocorrosion of ZnO.